Re-Examining the History of the Russian Economy A New Analytic Tool from Field Theory (Springer International Publishing, 2018)
This book explores the application of field theory (patterns of interaction) to Russian economic history, and how social and political fields mediate the influences of institutions, structures, discourses and ideologies in the creation and dissemination of economic thinking, theory and practice. Using focused cases on Russia's economy from the mid-nineteenth century to the present, Hass and co-authors expand the empirical basis of field studies to provide new material on Russian economic history. The cases are divided into two complementary halves: i) The role of fields of institutions, discourses, and structures in the development of Russian economic thought, especially economic theories and discourses; and ii) The role of fields in the real adoption and implementation of policies in Soviet and Russian economic history. With developed discussion of fields and field theory, this book moves beyond sociology to demonstrate to other disciplines the relation of fields and field theory to other frameworks and methodological considerations for field analysis, as well as providing new empirical insights and narratives not as well-known abroad. Jeffrey Hass is Associate Professor at the University of Richmond, USA, and St. Petersburg State University, Russia. His areas of expertise are economic sociology, political sociology, political economy, social change, sociology of power, organizational sociology, and comparative/historical sociology. He has published on post-socialism, including Rethinking the Post-Soviet Experience: Markets, Moral Economies, and Cultural Contradictions of Post-Socialist Russia with Palgrave Macmillan in 2011. He is currently continuing this line of work on post-socialist political economy, as well as investigating the politics and practices of survival in the Blockade of Leningrad.